Halal Marketplace Transaction Contracts in Indonesia: Fiqh Muamalah Perspective - Ali Mutaufiq (International Journal of Sharia Business Management, 2026)
This study aims to review and analyze the conformity of transaction contracts implemented in halal marketplaces in Indonesia with the principles of fiqh muamalah. The research focuses on identifying the types of contracts applied in halal marketplace transactions—such as sale and purchase contracts, payment mechanisms, and delivery systems—and evaluating their compliance with Islamic legal requirements, including transparency (clarity of object), mutual consent, and the absence of prohibited elements such as riba, gharar, and maisir. This research employs a qualitative approach using a literature review and normative juridical analysis. Primary data are derived from classical and contemporary fiqh muamalah sources, fatwas of the National Sharia Council (DSN-MUI), and relevant regulations, while secondary data include academic journals, books, and reports related to halal e-commerce practices in Indonesia. The findings indicate that most transaction contracts in halal marketplaces are generally aligned with fiqh muamalah principles, particularly through the application of bai‘, wakalah, and ijarah contracts. However, several challenges remain, especially regarding standard contract transparency, payment intermediaries, and dispute resolution mechanisms. The study concludes that although halal marketplaces in Indonesia largely comply with Islamic legal principles, continuous supervision and refinement of contract structures are necessary to ensure full sharia compliance in digital transactions.